ANALISIS BENTUK PELAFALAN FONETIK DAN AKSEN KATA GAIRAIGO PADA PEMBELAJAR BAHASA JEPANG - Fadia Nafa Anisah; Arza Aibonotika; Dini Budiani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: One things that often happens to foreign language learners, is always bring their nature of the mother tongue to the second language they use, especially when speaking in a foreign language. In Japanese language there are loanwords that come from foreign languages, this loanword has been adapted to suit Japanese sounds and accent. Japanese language is a pitch accent language, the meaning of each word depends on the shape of accent pattern, as well as the phonetics. This research was conducted with the aim of knowing what phonetics and accent that learner use when pronounced gairaigo word. This study uses a descriptive qualitative method, words spoken by 15 students of Japanese Language from Riau University. This study focuses on the pronunciation of loanwords from English, analyzed using a PRAAT device. The results is that students tend not to pronounce gairaigo word with Japanese sounds and accent. On phonetics, it is known that students tend not to pronounce words with the appropriate number of mora, not to pronounce obstructed nasal consonants [N], long vowels(cho’on), and consonant clusters (saku’on). On Accents, it is known that students tend to use Indonesian accents.Key Words: Pronunciation, loanword (gairaigo), phonetic, accent